ANALYSIS OF THE PROSECUTOR'S WIREBREAKING AUTHORITY IN HANDLING TERRORISM CRIMES - Kadek Sudhi Asthawa; Sujono; Rizky Pratama Putra Karo Karo (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
This study analyzes the Attorney General's authority to wiretap in handling terrorism crimes from the perspective of the principle of justice in the Pancasila rule of law and its implications for the protection of human rights. Wiretapping is an exceptional and intrusive law enforcement instrument because it limits the right to privacy and confidentiality of communications. Therefore, its implementation must be based on clear authority, strict legal procedures, and effective oversight mechanisms. This study uses a normative legal research method with a statutory, conceptual, and analytical approach. The analysis was conducted on the Attorney General's Law, the Law on the Eradication of Terrorism Crimes, the new Criminal Procedure Code, and human rights protection instruments. The analytical framework uses the Pancasila rule of law theory, the theory of authority, and the theory of the right to privacy. The results of the study indicate that the Indonesian legal system positions wiretapping as a coercive measure that can only be carried out by institutions that have express authority from the law. The Attorney General's law enforcement intelligence authority does not explicitly include wiretapping authority. In the practice of counterterrorism, the Attorney General's Office plays more of a role as a user of wiretapping results. This lack of clarity in regulations has the potential to create legal uncertainty and the risk of human rights violations. Therefore, regulatory clarification and harmonization are needed to ensure that wiretapping authority aligns with the principles of justice, the Pancasila state based on law, and the protection of human rights.